Understanding lung cancer : tobacco smoking linkage - Roy, Priyanka; Laha, Arnab Kumar (London : SAGE Publications Ltd, 2017)
Lung cancer is a common type of malignant neoplasm affecting people across the globe. It has claimed many lives till date. The rate of death due to lung cancer is highest among cancer death cases in developed countries and it is also increasing at an alarming rate in developing nations. The main cause of lung cancer is presumed to be the long term exposure to smoking of tobacco, as tobacco smoke contains a huge number of cancer causing elements i.e. carcinogens. The other causes can be genetic factors, exposure to asbestos, radon gas, passive smoking etc. Dr. Diya Sharma, an epidemiologist at the Pragmatic Medical Research Centre, was deeply involved in a research on lung cancer during the spring of 2013. She was trying to find out whether the incidence of lung cancer was significantly correlated with the smoking habit. She looked up previously done research works that related lung-carcinoma with smoking and found some relevant studies done in Great Britain. After going through some datasets showing the occurrence of lung cancer and death due to it in Great Britain, she was surprised to see that, for some years after 1922, there was an exceptional increase in the number of deaths due to lung cancer in Great Britain. This sudden rise in mortality rate led health care personnel to consider the fact that the patients who contracted lung cancer were also tobacco smokers. Even though this was a common perception, these personnel required scientific proof to justify their observation.
Originally published: Roy, P., & Laha, A. K. (2014). Understanding lung cancer: Tobacco smoking linkage. CMHS0028. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Sharma, Diya, -- Dr; Pragmatic Medical Research Centre; Lungs -- Cancer -- Great Britain -- Case studies; Lungs -- Cancer -- Diagnosis -- Great Britain -- Case studies; Caracinogens -- Great Britain -- Case studies